2017
DOI: 10.1111/jcpe.12805
|View full text |Cite
|
Sign up to set email alerts
|

Open flap debridement of peri‐implantitis with or without adjunctive systemic antibiotics: A randomized clinical trial

Abstract: Surgical treatment of peri-implantitis with adjunctive systemic azithromycin did not provide 1-year clinical benefits in comparison with those only receiving open flap debridement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
148
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(160 citation statements)
references
References 31 publications
9
148
1
2
Order By: Relevance
“…Still, the outcomes observed in this study concerning pocket depth reduction (2.19 mm) and mean bone gain (0.91 mm) are a little higher than the ones reported by Hallström, Persson, Lindgren, and Renvert (2017) after an open flap debridement approach. They achieved a mean probing depth reduction of 1.7 mm in the test group and of 1.6 mm in the control group, and a mean bone gain of 0.6 mm and 0.4 mm in the test and control groups, respectively.…”
Section: Discussioncontrasting
confidence: 79%
“…Still, the outcomes observed in this study concerning pocket depth reduction (2.19 mm) and mean bone gain (0.91 mm) are a little higher than the ones reported by Hallström, Persson, Lindgren, and Renvert (2017) after an open flap debridement approach. They achieved a mean probing depth reduction of 1.7 mm in the test group and of 1.6 mm in the control group, and a mean bone gain of 0.6 mm and 0.4 mm in the test and control groups, respectively.…”
Section: Discussioncontrasting
confidence: 79%
“…These findings are in accordance with the findings of previous studies. 7,8,32,33 To the best of our knowledge, there is no human study in literature for a direct comparison of the results of the CGF group. Therefore, this is the first clinical study evaluating the additional use of CGF as a resorbable membrane compared with the use of CM with a bonegrafting material for the reconstruction of PBD.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Recent systematic reviews of clinical trials have reported that regenerative surgical treatment (RST) of peri-implantitis has been shown to result in improvements in probing depth (PD) reduction, BOP and radiographic evidence of defect fill (DF). [3][4][5][6][7][8] Recent systematic reviews of clinical trials have reported that regenerative surgical treatment (RST) of peri-implantitis has been shown to result in improvements in probing depth (PD) reduction, BOP and radiographic evidence of defect fill (DF).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence suggests these methods may not be sufficient and results may be similar to conventional debridement 38,39,40,41 Comparing results of open flap debridement of peri-implantitis with and without adjunctive systemic antibiotics demonstrated there was no significant difference in benefits with using the antibiotics 42 The criteria for success in this study was also pocket probing depths of < 5mm which provides an environment where facultative and obligate anaerobes may become the predominant species 43,44 .…”
Section: Introductionmentioning
confidence: 92%